EEF-2 Kinase-targeted miR-449b confers radiation sensitivity to cancer cells. (1st April 2018) - Ji, Cheng; Xu, QiongHua; Guo, LingChuan; Wang, XiaoHui; Ren, YiJie; Zhang, HongHan; Zhu, WeiDong; Ming, ZhiJun; Yuan, YunSheng; Ren, XingCong; Song, JianXun; Cheng, Yan; et al.
Abstract: The roles of microRNA in regulation of various biological processes and in modulation of therapeutic effects have been widely appreciated. In this study, we found a positive correlation between miR-449 b expression and radiation sensitivity in cancer cells and in tumor specimens from patients. We showed that eEF-2 kinase, a negative regulator of global protein synthesis, is a target of miR-449 b. Introducing a miR-449 b mimic into cancer cells led to suppression of eEF-2 kinase expression, leading to increases of protein synthesis and depletion of cellular ATP. Further, we demonstrated that the miR-449 b mimic rendered the cancer cells more sensitive to ionizing radiation both in vitro (cell culture) and in vivo (animal xenograft model). Moreover, the radiation sensitivity conferred by miR-449 b could be blunted by cycloheximide, an inhibitor of protein synthesis, or by direct delivery of ATP liposome, supporting eEF-2 kinase as a mediator of the radio-sensitizing effects of miR-449 b. These results indicate that miR-449 b, which is frequently down-regulated in radio-resistant cancers, may represent a new critical determinant of radio-sensitivity. Highlights: A positive correlation exists between miR-449b expression and radiation sensitivity in cancer cells and patients specimens. miR-449b renders the cancer cells more sensitive to ionizing radiation. miR-449b functions as a novel radio-sensitizer in cancer. miR-449b confers radiation sensitivity to cancer cells by direct targeting EEF2K. Our findings add a novel pathway involved in modulating radiotherapy sensitivity in cancer.